Reclassifying inconclusive diagnosis for cystic fibrosis with new generation sweat test. Issue 2 (4th August 2022) - Nguyen-Khoa, Thao; Hatton, Aurélie; Drummond, David; Aoust, Laura; Schlatter, Joël; Martin, Clémence; Ramel, Sophie; Kiefer, Sébastien; Gachelin, Elsa; Stremler, Nathalie; Cosson, Laure; Gabsi, Asma; et al.
The biological diagnosis of cystic fibrosis (CF) is based on a sweat chloride (Cl − ) concentration (SCC) ≥60 mmol·L −1 and/or the identification of two allelic CF-causing variants [1]. Diagnosis of CF can be challenging in subjects with intermediate SCC between 30 and 59 mmol·L −1 and only one CF-causing variant detected. The evaporimetric beta-adrenergic sweat secretion test is feasible, safe, and accurate. It provides a valuable complementary test for proper classification of patients with CF-like symptoms presenting borderline SCC but inconclusive genetic test results. https://bit.ly/3vMyXx5